Implications of Employees Behaviour In Tourism Industries: Exploring the Impact of HRM Practices on Employee Behavior in Tourism Industries (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Dogood, get good, is the new human resource management mantra. Every bit of thehuman resource of any organization has to be respected and bestowed withbefitting HRM practices to generate service oriented behaviours for fantasticand phenomenal success in the global tourism. So, this study has practical andpolicy implications for the organizations, and service organizations inparticular. Organizations can certainly make significant improvements to theirperformance by emphasizing excellent human resource management practices.Research papers, articles, newspapers, books, internet etc. are all floodedwith dialogues on globalization. In fact, it is no exaggeration. It is thecatch word now-a day. The massive change in the style and structure ofbusinesses has further strengthened the belief that globalization is headingits way for even bigger dimensions and at an ever increasing pace. Economiesare witnessing a new face of competition. In a fast-paced, globally competitiveeconomy, efforts to boost productivity and quality never end (Cascio, 1998).The Indian government companies need to learn from the practices adopted by theprivate/multinational companies especially with regard to competitivecompensation, selection and socialization of employees, and contemporary HRpractices. Gone are the days when experience was the basis for decidingseniority, which in turn was the basis for deciding compensation.